Tectonic evolution of the Gabal Loman area, North Eastern Desert, Egypt: implications from low-temperature multithermochronometry on the Arabian-Nubian shield - Mansour, Sherif; Gharib, Mohamed A.; Hasebe, Noriko; Abdelrahman, Kamal; Fnais, Mohammed S.; Tamura, Akihiro (Frontiers in Earth Science, 2023)
The Neoproterozoic Arabian-Nubian Shield (ANS) in the Eastern Desert of Egypt encloses the regional thermal-tectonic history from its development till the Oligo-Miocene when the Red Sea rift system was initiated. The application of multi-thermochronometry techniques has proven to be a successful approach to revealing the influence and extent of each regional tectonic event and the recreation of the tectono-thermal development of the studied region through time. Therefore, characteristic samples from the ANS different rock suits of the Gabal Loman area at the western flank of the northern Red Sea were collected. The Zircon fission-track data reveals the Carboniferous cooling ages, while the apatite fission-track cooling ages present two differential time spans of Cretaceous and Eocene-Oligocene. The time-temperature history modeling is integrated with fission-track data to reveal three differentiated cooling events developed in response to regional tectonic events: 1) the Hercynian (Variscan) tectonic event that influenced the ANS vicinity with rock uplifts of ca. 4 km through the Devonian-Carboniferous time, 2) the Gondwana disintegration event which influenced the region with differential rock exhumations, and 3) the northern Red Sea rifting through the Oligo-Miocene which caused a regional ca. 1 km of rift flanks exhumation. This modest rift flank uplift suggests a passive rift of the northern Red Sea rifting in the region of study.